Why the Co-based 115 compounds are different: The case study of GdMIn5 (M = Co,Rh,Ir) - Facio, J.I.; Betancourth, D.; Pedrazzini, P.; Correa, V. F; Vildosola, V.; García, D. J.; Cornaglia, P.S.; Correa, Víctor Félix; Pedrazzini, Pablo (American Physical Society, 2015)
Fil: Facio, J.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina